Changes in training patterns and confidence to return to sport in United States collegiate athletes during the COVID-19 pandemic - Seligman, E.; Beasley, M. A.; Christino, M. A.; Miller, P. E.; Kobelski, G.; Stracciolini, A. (The Physician and Sportsmedicine, 2023)
Objective To describe the training patterns, return to sport (RTS) confidence, and perceived fitness during the COVID-19 pandemic summer 2020 and to compare training patterns and RTS readiness during COVID-19 versus during the 2019 summer in a cohort of Division III collegiate athletes.